Elderly Participation in Elderly POSYANDU in Relationship with Family Support - Wiwis Kiswati; Ira Titisari; Siti Aisyah (STIKes Patria Husada Blitar, 2022)
In 2020, there are an estimated 727 million elderly over worldwide. In Indonesia, according to the East Java Health Profile, it is stated that the coverage of the elderly who received health services in 2019 was 62.9% of the 5,221,188 elderly (East Java Provincial Health Office, 2020) which is very far from the minimum standard for elderly posyandu services, which is 80%. The purpose of this study was to see whether there was a relationship between the involvement of the elderly in the posyandu for the elderly with family support. The Elderly Posyandu is one of the services for the elderly which includes prevention, improvement, treatment, and healing activities. This study was conducted to see whether there is a relationship between the participation of the elderly in the posyandu for the elderly in relation to support from the family. This writing uses a systematic mapping review design. Using the keywords â€œElderlyâ€ AND â€œFamily Supportâ€ AND â€œParticipation in Elderly Posyanduâ€ OR â€œFamily Supportâ€ AND â€œElderlyâ€ AND â€œHealth Servicesâ€. This writing uses a comparison technique. 10 articles were selected using CASP tools and JBI tools. Articles were taken from the Google Scholar database (1 journal), PubMed (2 journals), e-Journal (2 journals), Garuda (3 journals), and Researchgate (2 journals). There is a relationship between the actions of the elderly in attending the posyandu for the elderly with family support, which consists of instrumental assistance, information assistance, assessment assistance, and emotional assistance. From the results of the analysis, it has been found that there is a relationship between the participation of the elderly in the elderly posyandu in relation to family support. We hope that these findings can be used as a basis for analyzing plans to improve health for the elderly